2014
DOI: 10.1155/2014/218769
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Exogenous Gonadotropin Stimulation on Circulatory and Follicular Fluid Cytokine Profiles

Abstract: Background. The natural cycle is the prototype to which we aspire to emulate in assisted reproduction techniques. Increasing evidence is emerging that controlled ovarian hyperstimulation (COH) with exogenous gonadotropins may be detrimental to oogenesis, embryo quality, and endometrial receptivity. This research aimed at assessing the impact of COH on the intrafollicular milieu by comparing follicular fluid (FF) cytokine profiles during stimulated in vitro fertilization (IVF) and modified natural cycle (MNC) I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 82 publications
1
7
0
Order By: Relevance
“…Cytokine-cytokine receptor interactions and the TNF signaling pathway were all functionally enriched among up-regulated DEGs. Inconsistent with the results obtained from a previous study, Baskindet al [22], reported that the majority of circulatory cytokines, such as IL8, were present at higher concentrations in the modified natural-cycle cohort than in the COH group. Kollmann et al [20] also reported that FF contained a marginally lower concentration of IL8 under a stimulated cycle than a natural cycle.…”
Section: Discussionsupporting
confidence: 80%
“…Cytokine-cytokine receptor interactions and the TNF signaling pathway were all functionally enriched among up-regulated DEGs. Inconsistent with the results obtained from a previous study, Baskindet al [22], reported that the majority of circulatory cytokines, such as IL8, were present at higher concentrations in the modified natural-cycle cohort than in the COH group. Kollmann et al [20] also reported that FF contained a marginally lower concentration of IL8 under a stimulated cycle than a natural cycle.…”
Section: Discussionsupporting
confidence: 80%
“…Nevertheless, in stimulated ICSI cycles the FF IL-15 concentrations are negatively correlated with the follicle size and with the maturity of the corresponding retrieved oocytes, suggesting that in stimulated ICSI cycles FF IL-15 could be a possible negative predictor for oocyte maturity ( 66 ). Again, we could hypothesize that stimulation with exogenous gonadotrophins could significantly perturb the intrafollicular cytokine network, impacting oocyte maturation/fertilization and embryo developmental competence ( 67 ).…”
Section: Discussionmentioning
confidence: 99%
“…15 Ovarian stimulation results in more oocytes as well as supraphysiological estradiol, progesterone, and cytokines. 22,23 The endometrium and implanting embryo in the fresh transfer cycles immediately after ovarian stimulation are subject to altered internal environment. 24 Laboratory studies have suggested that endometrium in the fresh cycles was different from that in natural ovulation cycles in terms of histological development, gene expression, and immunological responses, which may denote impaired endometrial receptivity.…”
Section: Pregnancy Pregnancy Loss and Live Birthmentioning
confidence: 99%